Mobile Augmented Reality Storybook Embedded with Local Wisdom: A Needs Analysis of Primary Students in Learning English - Asih Rosnaningsih; Asep Muhyidin; Sholeh Hidayat; Yudi Juniardi (Universitas Islam Negeri Palopo, 2025)
This research investigated the development of a Mobile Augmented Reality (MAR) English storybook embedded with local wisdom to support English learning in primary schools. It focusses to analyse the necessities, lacks, and wants of students and teachers regarding technology-based learning media and to design a preliminary concept of a MAR storybook appropriate for young learners. A qualitative needs analysis was conducted with 50 fourth-grade students and 2 English teachers in primary school in Serang City, Banten Province, Indonesia. Data were collected through questionnaires, interviews, and classroom observations to examine students’ learning habits, teachers’ perspectives, and classroom challenges. The results showed that the majority of students (52% are accustomed to using smartphones, 57% are very familiar with technology, 67% like story-based learning, and 76% are enthusiastic about interactive animation) and teachers need contextual, interactive, and easily accessible learning media, while the shortcomings due to limited infrastructure, teacher training, and the dominance of memorization methods. As a solution, a pre-designed MAR storybook was developed based on Bantenese folktale with simple text, illustrations, audio, AR animation, as well as vocabulary, pronunciation, reflective quizzes, and critical question features in a lightweight, child-friendly application that can be accessed online and offline.